Komunikasi Terapeutik Perawat Dalam Menunjang Kesembuhan Pasien Anak Di Rumah Sakit Bhakti Medicare Cicurug - Aris Zuliansyah (STISIP Widyapuri Mandiri Sukabumi, 2023)
Therapeutic communication is effective in influencing human behavior and implementing health services in hospitals. The nurse's ability and understanding in therapeutic communication is considered to be lacking. This study aims to determine the stages of nurse therapeutic communication in supporting the recovery of pediatric patients, through observation, interviews, documentation and triangulation techniques. The results showed that the pre-interaction and work stages were going well, but there were still deficiencies in medical language and the screening and termination stages had been running quite optimally.